2014
DOI: 10.2175/106143013x13807328849297
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Microbial Community in the Rhizosphere ofPhragmites australis(Cav.) Trin ex. Steudel Growing in the Sun Island Wetland

Abstract: Rhizospheric microorganisms are important for environmental conservancy. The constancy and variability of the microorganisms in the rhizosphere of Phragmites australis in relation to the spatiotemporal variations in wetland ecosystems were studied. During the peak and trough of the vegetative period of the Phragmites australis growing across the hydrologic gradients of the Sun Island Wetland, Biolog and denaturing gradient gel electrophoresis (DGGE) were used to investigate the rhizospheric microbial character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…The Gleysol analysed by Wolińska et al [51] was more acidic (pH~5.9) than that analysed here. Literature reports indicate that soil microbiomes may be dependent on both soil type and pH [6,[56][57][58]. All organisms of the Thaumarcheota identified are chemolithoautotrophic ammonia-oxidisers, may play important roles in biogeochemical cycles, and are among the most abundant archaea on Earth [59,60].…”
Section: Microbial Metabolic Potential and Bacterial Community Composmentioning
confidence: 99%
“…The Gleysol analysed by Wolińska et al [51] was more acidic (pH~5.9) than that analysed here. Literature reports indicate that soil microbiomes may be dependent on both soil type and pH [6,[56][57][58]. All organisms of the Thaumarcheota identified are chemolithoautotrophic ammonia-oxidisers, may play important roles in biogeochemical cycles, and are among the most abundant archaea on Earth [59,60].…”
Section: Microbial Metabolic Potential and Bacterial Community Composmentioning
confidence: 99%
“…Enhanced specific activities of nitrogen-cycling enzymes accompanied by bacterial density-dependent behaviors in the rhizosphere soil suggest that AHL could be a control point in the complex process of rhizosphere nitrogen mineralization (DeAngelis et al, 2008; Lamers et al, 2012). Furthermore, AHL molecules can affect plant gene expression and physiological features such as growth rate, root development, and resistance to microbial pathogens (Scott et al, 2006; Ma et al, 2014). More recently, the presence of AHL signaling molecules in soil microbes can affect the production of extracellular hydrolytic enzymes, suggesting that AHLs may take part in population communications and co-exist behaviors, especially in plant and other complex environments (Crevelin et al, 2013; Jayaraman et al, 2014; Schikora et al, 2016; Venturi and Keel, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Differences in the physicochemical properties and nutrient elements of soil inevitably affect crop quality and yield (Jun et al., 2021), and these differences depend to some extent on the biochemical processes of microbial activity in the soil ecosystem (Girvan et al., 2003). Studies have shown that soil physicochemical properties and soil‐forming parent materials, such as pH, salinity, and type, have a very important impact on the development of certain bacterial taxa (Ma et al., 2014).…”
Section: Introductionmentioning
confidence: 99%